Effectiveness, adverse drug reactions and adherence among hypertension patients in department of general medicine at Integral Institute of Medical Science and Research: a prospective observational study - Mahfooz, M. Sahil; Husain, Manauwar; Roy, Mukul; Fatima, Kashefa; Akhter, M. Sohel; Khan, M. Tauseef (International Journal of Basic & Clinical Pharmacology, 2025)
Background: This study aimed to evaluate the drug effectiveness, adverse drug reactions and adherence among hypertensive patients. Additionally, we aimed to determine the clinical characteristics and the risk factors. Methods: This six-month prospective observational study was jointly conducted by Integral University’s department of pharmacy and Medicine at Integral Institute of Medical Sciences and Research, Lucknow. The investigation involved 100 hypertensive patients from both inpatient (IPD) and outpatient (OPD) departments. Collected data were analysed through Microsoft Excel using descriptive statistical methods. Results: The study population comprised 100 hypertensive patients (38 male, 62 female). Analysis showed 82% treatment efficacy, with telmisartan+amlodipine combination therapy achieving significant blood pressure reduction (11.7 mmHg). Notably, ADRs were monitored via active surveillance and patient interviews; suspected events were assessed using the Naranjo causality scale. Medication compliance reached 84%, particularly with once-daily regimens of amlodipine 5 mg and telmisartan 40 mg (marketed as Telvas/Telma). These findings demonstrate the clinical efficacy and safety profile of current antihypertensive protocols, emphasizing the importance of appropriate drug selection and dosing schedules. Conclusions: The study confirmed the therapeutic effectiveness, strong adherence rates, and excellent safety profile of antihypertensive treatments, particularly telmisartan and amlodipine. These outcomes validate existing prescription patterns while providing real-world evidence for hypertension management strategies. Ongoing monitoring of treatment response and patient compliance remains crucial for maintaining optimal cardiovascular health outcomes.